TEORI SIKLUS EKONOMI IBNU KHALDUN : ANALISIS DALAM KONTEKS KRISIS EKONOMI - Aisyiah, Rohadatul; Marwa melati, Suryani; Azim Mubarak, A.M. Syahruk (Universitas KH. A. Wahab Hasbullah, 2024)
In the economic field, Ibnu Khaldun's ability to explain economic concepts was very sharp. Economic problems were discussed by Ibnu Khaldun in his book which discussed economic motives arising because human desires are unlimited, so the goods that will satisfy their needs are very limited. Therefore, to solve economic problems it must be seen from two angles; power angle and from the point of use. The purpose of writing this article is to understand Ibn Khaldun's economic cycle and analyze the modern economic crisis. The research method used is literature study, which is a method of searching and researching literature by reading various books, journals and other publications related to the research topic, to produce an article regarding a particular topic or issue. The results of the research found that Ibn Khaldun had provided the concepts and practices of Islamic economics and had made contributions and treasures of Islamic knowledge to economics in general and Islamic economics in particular.